Mechanism of Crystallographic Orientation and Texture Evolution of Ti60 Alloy during Plane Strain Compression - Yi Dai; Yunteng Xiao; Weidong Zeng; Runchen Jia; Weiju Jia (Metals, 2024)
The crystallographic orientation and texture evolution mechanism of equiaxed Ti60 alloy plates were investigated in this study through plane strain compression tests. The EBSD analysis revealed that the received plate contained two characteristic textures that were perpendicular to each other, i.e., c-axis//TD (Component 1) and c-axis//RD (Component 2), with the latter being caused by the change in direction of the TD texture that was generated during the previous unidirectional rolling process into an RD direction in the cross-rolling process. The results demonstrated that, with increasing the deformation temperature from 930 °C to 960 °C and 990 °C, the intensity of the c-axis//TD texture (Component 1) initially rose to a peak value of 5.07, which then—subsequently—decreased significantly to 2.96 at 960 °C and 3.11 at 990 °C. Conversely, the intensity of the c-axis//RD texture (Component 2) remained relatively unchanged. These texture changes were correlated with slip system activity and the spheroidization of the primary alpha phase. For the c-axis//TD texture, the initial intensity of the texture components during compression at lower temperatures could be attributed to the incomplete dynamic spheroidization process of the α phase, which leads to the reinforcement of the c-axis//TD due to prismatic slip. As the deformation temperature increased, the dynamic spheroidization process became more prominent, thereby leading to a significant reduction in the intensity of the c-axis//TD texture. In contrast, the c-axis//RD texture exhibited difficulty in activating the prismatic slip and basal slip; in addition, it also encountered resistance to dynamic spheroidization, thus resulting in negligible changes in the texture intensity.